1996
DOI: 10.1002/jor.1100140421
|View full text |Cite
|
Sign up to set email alerts
|

Optimal normalization tests for shoulder muscle activation: An electromyographic study

Abstract: To accurately compare electromyographic data from different muscles and different subjects, it is necessary to normalize the integrated data obtained from each muscle. The purpose of this study was to identify the manual muscle testing positions that elicit maximal neural activation (integrated electromyography) of three rotator cuff muscles (supraspinatus, infraspinatus, and subscapularis) and five shoulder synergists (pectoralis major, latissimus dorsi, and anterior, middle, and posterior deltoids). The elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
1
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 15 publications
5
67
1
5
Order By: Relevance
“…Three of the four suggested Shoulder Normalization Tests were previously described by these authors. Our results support those of Kelly et al 2 for the ''empty can'' test, finding it maximally activated supraspinatus, anterior deltoid, and middle deltoid, and the ''internal rotation 908'' test which maximally activated subscapularis (upper and lower parts in the current study) and latissimus dorsi. Our results differed from Kelly et al 2 in that the ''empty can'' test was better able to maximally activate the posterior deltoid than the ''external rotation at 908'' abduction identified by these authors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Three of the four suggested Shoulder Normalization Tests were previously described by these authors. Our results support those of Kelly et al 2 for the ''empty can'' test, finding it maximally activated supraspinatus, anterior deltoid, and middle deltoid, and the ''internal rotation 908'' test which maximally activated subscapularis (upper and lower parts in the current study) and latissimus dorsi. Our results differed from Kelly et al 2 in that the ''empty can'' test was better able to maximally activate the posterior deltoid than the ''external rotation at 908'' abduction identified by these authors.…”
Section: Discussionsupporting
confidence: 92%
“…Our results support those of Kelly et al 2 for the ''empty can'' test, finding it maximally activated supraspinatus, anterior deltoid, and middle deltoid, and the ''internal rotation 908'' test which maximally activated subscapularis (upper and lower parts in the current study) and latissimus dorsi. Our results differed from Kelly et al 2 in that the ''empty can'' test was better able to maximally activate the posterior deltoid than the ''external rotation at 908'' abduction identified by these authors. Furthermore, Kelly et al 2 did not examine the ''palm press'' test and concluded that internal rotation at 08 abduction was the most effective test for pectoralis major.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A total of four muscle tests were performed following the methods described by Boettcher et al [22] and Kelly et al [23]. The test order was block randomized.…”
Section: Maximum Voluntary Isometric Testmentioning
confidence: 99%